2022
DOI: 10.12669/pjms.38.5.5207
|View full text |Cite
|
Sign up to set email alerts
|

Reliability of hand-held dynamometer in measuring gluteus medius isometric muscle strength in healthy population

Abstract: Objectives: To determine the inter-rater and intra-rater reliability of the hand-held dynamometer in measuring isometric gluteus medius muscle strength in asymptomatic healthy population. Methods: It was a cross sectional study conducted at the department of physiotherapy, Sindh Institute of Physical Medicine and Rehabilitation from March 2021 to April 2021. Thirty healthy subjects aged 18 to 25 years of both sexes and no previous or current complaints of hip or knee pain were included through non-probab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 19 publications
0
6
0
Order By: Relevance
“…In relation to this, it is suggested that participating in Salaah movements may positively impact the muscle strength of the knee extensors. Skou et al 31have also recommended that repetitive knee extensor movements play a role in minimising the risk of developing knee pathologies 32…”
Section: Discussionmentioning
confidence: 99%
“…In relation to this, it is suggested that participating in Salaah movements may positively impact the muscle strength of the knee extensors. Skou et al 31have also recommended that repetitive knee extensor movements play a role in minimising the risk of developing knee pathologies 32…”
Section: Discussionmentioning
confidence: 99%
“…Two certified ATs will be acquiring the measurements. Hand-held dynamometry has been shown to be a valid [ 56 ] and highly reliable tool to assess gluteus muscle strength [ 57 ] and has been recommended as a practical standard for clinical setting.…”
Section: Methodsmentioning
confidence: 99%
“…The manual muscle testing protocol was used to assess strength of the tibialis posterior (Barn et al, 2012), flexor hallucis brevis (Yazici et al, 2020), and GMed (Soomro et al, 2022) by a handheld dynamometer. From our pilot study, an excellent intrarater reliability was found for this measurement in this study (ICC (3,3) of 0.85 to 0.97).…”
Section: Muscle Strength Assessmentmentioning
confidence: 99%